Gestão da informação no laboratório de acessibilidade da Biblioteca Central Zila Mamede da Universidade Federal do Rio Grande do Norte - Oliveira, Gabriella Domingos de (2017)
Information Science studies the informational paradigms and it is concerned with the subject of information, that is, the one who creates, shares and uses information. As a scientific field that assists the mediation of information for society, this science also targets to intermediate the inclusive information and to attend to the diversity and the profiles of users, especially when talking about information as object of meaning and interpretation for the Informational subject. The collection, dissemination and use of information have become a essential processes in the professional, social and personal life of individuals for both informational / social inclusion and for the accomplishment of activities. In this context, the general objective of this research is to analyze the information management processes in the Accessibility Laboratory of the Zila Mamede Central Library of the Federal University of Rio Grande do Norte, from the perspective of the Choo model (2011), aiming at the informational accessibility of students with visual impairment. This field research has a qualitative approach, whose data were collected through a semi-structured interview applied to 14 subjects, among managers, employees, scholars and laboratory users, and analyzed based on the content analysis method. The results revealed that the respondents presented common informational needs for the accomplishment of the activities, however, also, there are specific demands. The higher the hierarchical position, the more information sources are used to carry out the activities in the laboratory. In the organization, storage, retrieval and distribution of information by the respondents the digital form prevails. There is a certain lack of knowledge regarding the products and services offered by the unit, since some of the subjects only know those who use them more frequently, and also a communication problem which affects the delivery of material to the users of the laboratory, that doesn´t share the information received, only stores it for its own use.